Seed yam production using high-quality minitubers derived from plants established with vine cuttings - Aighewi, B.; Maroya, N.; Kumar, P. Lava; Balogun, M.; Aihebhoria, D.; Mignouna, Djana B.; Asiedu, R. (MDPI, 2021)
Yam (Dioscorea spp.) is a valuable food security crop in West Africa, where 92% of the world production occurs. The availability of quality seed tubers for increased productivity is a major challenge. In this study, minitubers weighing 1, 3, and 5 g produced from virus-free single-node vine cuttings of two improved yam varieties (Asiedu and Kpamyo) growing in an aeroponics system were assessed for suitability in seed production at a population of 100,000 plants ha−1. A 3 × 2 factorial experiment with randomized complete block design and three replications was set up during the cropping seasons of 2017 to 2019 at the International Institute of Tropical Agriculture Research Station in Kubwa, Abuja, Nigeria. Results showed field establishments of 87%–97.8%. Yields differed with minituber size, variety, and cropping season; the highest was 31.2 t ha−1 in 2019 and the lowest, 10 t ha−1 in 2018 from 5 and 1 g Kpamyo minitubers, respectively. The estimated number of tubers produced per hectare by 1, 3, and 5 g minitubers was 101,296, 112,592, and 130,555, with mean weights per stand of 159.2, 187.3, and 249.4 g, respectively. We recommend using less than 6 g minitubers for seed yam production due to their high multiplication rates.